PENGARUH BRAND IMAGE DAN GAYA HIDUP TERHADAP KEPUTUSAN PEMBELIAN SEPATU MEREK CONVERSE (Studi Kasus Masyarakat Kelurahan Sawah Lebar Baru Kota Bengkulu) - Darmawan, Anton; Arini, Eti (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2024)
This study aims to determine the effect of brand image and lifestyle on purchasing decisions for Converse brand shoes (Case Study of the Community of Sawah Lebar Baru Village, Bengkulu City). This research uses quantitative research methods. The population in this study was the Sawah Lebar Baru Village Community, Bengkulu City, with the sampling method using the Purposive Sampling method. In the implementation of the research, 110 respondents were obtained randomly. In this study using data collection methods by way of observation, interviews and distributing questionnaires or questionnaires. The data that has been collected is then processed using an instrument test, analysis of respondents' responses, classic assumption test, multiple linear regression analysis, coefficient of determination (R2) and hypothesis testing using SPSS 20 Based on the results of multiple linear regression, Y = 4.313 + 0.889 (X_1) + 0.404 (X_2). The coefficient of determination R2 contributes 0.626 or 62.6% to purchasing decisions while the remaining 0.374 or 37.4% is influenced by other variables not included in this research model. The test results have been carried out, it can be seen that the brand image variable is thit> ttable (9.936 > 1.659) and (sig α = 0.000 <0.050), lifestyle variable (X2) is thit > ttable (4.152 > 1.659) and (sig α = 0.000 <0.050), obtained Fcount of 88.691 with a Ftable value of 3.08 namely (88.691 > 3.08) and (sig α = 0.000 <0.050). From the results of data processing, it can be concluded that brand image and lifestyle partially or simultaneously have a positive and significant effect on purchasing decisions. Keywords: brand image, lifestyle, purchase decisio